A Web-based Collaborative System Framework for Green Building Certification - Cheng, Jack C.P.; Venkataraman, Vignesh (International Journal of Sustainable Construction Engineering and Technology, 2013)
The built environment is moving towards sustainable development and the number of green buildings increased worldwide in recent years. Green buildings are environmentally, socially and economically desirable; however the certification of green buildings is often expensive and labor-intensive. The document preparation and review process for green building certification is iterative in nature and requires the collaboration of many project participants, certification organizations and third party engineering consultants. This paper aims at developing a system framework that can assist the green building certification process. Different certification standards have been studied and their scope and credit calculation were compared to understand the requirements of the system framework. Based on the study, the required features were designed as follows, (1) role-based access control, (2) document manager and related document discovery, (3) workflow manager, (4) credit manager, and (5) knowledge manager. The features of the system provide a collaborative environment and reduce repetitive works commonly occurring in manual processes. The features of the system framework are discussed and illustrated considering the Hong Kong BEAM Plus standard. This paper also describes how the system framework enhances collaboration in the certification process